« This narrative is my written memory » : transcrire la mémoire dans David Copperfield de Charles Dickens - Céline Prest (Cahiers Victoriens et Edouardiens, 2015)
David Copperfield as a fictitious autobiography appears to be a form of transcription, the faithful copy of the narrator’s experiences recorded from memory. However, such a transcription must be recognised as an artistic composition, since David Copperfield is the only Dickensian character to define himself as a writer. Anticipating Marcel Proust’s autobiographical masterpiece, David is in search of lost time. He exhumes the memories stored in his mind, which has become an archival space preserving the traces of the past. David first appears as the successor of the Greek arkheions whom Derrida defined as the keepers and interpreters of all official documents (of which the word ‘archive’ will be derived). This archivist is also an archaeologist, returning to previous traces by digging down through the strata of memory, unveiling the past to make it verbally emerge to the surface of the present. Through his words, David elevates a memory palace. He invokes the ghosts of past lives and loved ones, inviting them to haunt the novel along with him. The archivist turned archaeologist is finally transformed into an architect, the one who elevates monuments – these documents which bear the memory of the past.